What Should the Federal Government Be Doing About Urban Economic Development? - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 1994)
The federal government should focus its policies towards economic development on areas in which the federal government has some unique advantages. Federal policy should: (1) discourage financial subsidies to specific large firms by state and local governments; (2) expand the federal role in economic development services in which national action has some special advantages, such as developing information on foreign markets, encouraging large national banks to be more involved in economic development, supporting the development of the "Information Superhighway," and encouraging new technology development; (3) provide modest support for state and local efforts to increase business productivity through technology extension efforts and customized job training programs; (4) encourage more and higher quality evaluation of state and local economic development programs; (5) support experiments that link economic development efforts with hiring the disadvantaged; (6) relax federal regulations, such as regulations on the cleanup of older industrial sites, that impede local economic development.
Keywords: J4; R0; 330; urban; economic; development; federal; government; Bartik